Teknologi Dalam Proses Produksi Sumur Gas di Pertamina Hulu Mahakam Area South Mahakam - Endra Endra; Ida Rosanti; Diyaa Aaisyah Salmaa Putri Atmaja (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
Mahakam Working Area (WK Mahakam) is one of the largest oil and gas working areas in Indonesia managed by PT Pertamina Hulu Mahakam (PHM). WK Mahakam has large gas reserves, making it one of the largest contributors to national gas production. This study aims to determine the process of gas well production and know the technology used in the gas production process and know the efforts in increasing gas production in the Mahakam working area. The methods used are direct observation, interviews and literature studies. The results showed that the gas well production process consists of several stages, namely drilling, pipe installation, and gas processing.The technology used in the gas well production process includes directional drilling technology, horizontal drilling technology, Artificial Lift technology and Enhanced Oil Recovery technology. The efforts made by the company to increase gas production include exploration of new gas wells, development of gas production technology, improvement of production production, development of Artificial Lift technology, Enhanced Oil Recovery technology, a n d worker skills and implementation of digital technology.